Cubosomes- Advanced and Potential Nanolipid Carrier - S. Naveen Taj; K. Bhanu Sri Chandana (Challenges and Advances in Pharmaceutical Research Vol. 3, 2022)
Cubosomes are novel biocompatible and thermodynamically stable drug delivery systems; they have a microscopic structure like “honeycombed” with bi-continuous domains of water and lipid in which surfactant assembles into bilayers and arranged into a three dimension, periodic, and minimal surface, forming a tightly packed structure. Cubosomes have become an attractive choice of vehicle for in-vivo drug administration due to their low cost, safety, efficacy, and versatility for controlled release application and functionalization in the field of cosmeceuticals and pharmaceuticals due to their unique properties. Cubosome dispersions possess bio-adhesive and biocompatible nature. Based on their various properties, cubosomes are considered to be versatile systems and drug loaded formulations of cubosomes are administrable by different ways such as orally, percutaneously and parenterally. Overall, cubosomes have a lot of potential in nano-based medication formulations for cancer treatment, targeted distribution, and a wide range of other uses. In the pharmaceutical industry, cubosomes have taken a stride ahead in terms of awareness. This paper highlights the methods of preparation, advantages; different categories of drugs incorporated in cubosomesand its applications.